Quality of models supplied to dental laboratories for the fabrication of partial removable denture framework - MENEZES,Luma de Vasconcelos (2020)
ABSTRACT Objective The aim of this study was to evaluate the models and plannings of metallic framework of removable partial prosthesis sent to dental laboratories in the city of Recife. Methods: The physical and technical conditions of plaster models were sent by the dentists to 4 dental laboratories. All models were examined, photographed and recorded on a form according to the research objective. Results: A total number of 235 models sent by dental surgeons were used to prepare the metallic structure, in which none of the models presented surveying nor the path of insertion. Out of the 235 models, 41 (17.44%) presented serious failures, such as positive and negative bubbles, broken dental elements, direct retainers and damaged edentulous areas. With respect to the planning, only 22 (9.35%) models were presented with the metallic framework planning, but in an unsatisfactory way. Regarding mouth preparation, no model presented a guide plane, and only 6.8% of models had rests seats, but incorrectly prepared. Conclusion: The models evaluated presented poor quality, lack of planning and no mouth preparation. This shows the need for dental surgeons to be aware of the appropriate prosthesis models and plannings in order to ensure a satisfactory and long-term rehabilitation of the patient, as well as preserving the remaining mouth structures.